Benefits of Accounting Information Systems to Improve Service Quality at Regional General Hospital (RGH) dr. Agoesdjam Ketapang District - Haryaningsih, Sri; Elyta, Elyta; Nikodimus, Nikodimus; Apriyanto, Dhidik (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
This study aims to analyze the benefits of accounting information systems in improving service quality at the regional general hospital (RGH) dr Agoesdjam in Ketapang Regency. Accounting Information Systems in the current era serve as a source of information that presents financial reports on the company's performance over a period to both internal and external stakeholders. The research methodology employed in this study utilizes questionnaires, with primary data collected through the reception or responses of the respondents (sample). The survey was conducted by distributing questionnaires to 52 selected samples, chosen based on considerations that the samples adequately represent the characteristics of the entire population. The findings of this research indicate that the benefits of accounting information systems contribute to enhancing service quality at the regional general hospital (RGH) dr Agoesdjam in Ketapang Regency. The accounting information system plays a role in improving the quality of services by facilitating the timely completion of hospital administration tasks for both inpatient and outpatient services. The accuracy and speed of service provision reduce patient waiting times. The system is responsive in providing fast services, offering clear procedures, and presenting information to inpatients and outpatients in an easily understandable manner. In summary, the study underscores the pivotal role of accounting information systems in elevating the quality of services at the regional general hospital. The system enhances the efficiency of hospital administration, resulting in more accurate and prompt services, thereby minimizing patient wait times. The responsiveness of the system in delivering services and providing clear information contributes to the overall improvement in service quality at the hospital.